PERUBAHAN PERILAKU IBU TERHADAP STATUS GIZI BALITA MELALUI PELAKSANAAN PROGRAM POS GIZI - Neni Fitra Hayati; Hafizah R.; Novelasari M.Kes (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2023)
Proportion of malnutrition and malnutrition is at a percentage of 17.7% and is still above the target of 17%. The nutrition post program is one of the community empowerment-based innovation programs implemented in various regions in Indonesia to overcome nutritional problems. The purpose of the study was to see at changes in the behavior of mothers of toddlers towards nutritional status through the implementation of a nutrition post program. A type of quasi-experimental research with the research design of One Group Pretes Posttes, which was carried out in the working area of the Kuok Market Health Center, Pesisir Selatan Regency in May-June 2021. The study sample was 74 samples. Research measuring instruments are observation sheets, questionnaires and cheklist lists, data analysis with wilcoxon test and Chi-square test. Univariate results before and after the implementation of the nutrition post program were 10.90±1.91 and 11.46±1.98 for average body weight, 43.2% and 32.4% for the highest nutritional status, namely malnutrition. Bivariate results say there is a change in the mother's behavior towards the nutritional status of the toddler. It was concluded that the implementation of the nutrition post program provided a change in maternal behavior towards the nutritional status of the target toddler. It is recommended to puskesmas to increase the implementation of the nutrition post program. For researchers, in order to conduct further nutritional status checks, to see whether stunting or not toddlers are targeted.